A new species of Geholaspis Berlese (Acari: Mesostigmata: Macrochelidae) from Northern Iran - Babaeian, Esmaeil; Halliday, Bruce; Saboori, Alireza (Zootaxa, 2015)
Geholaspis (Geholaspis) pennulatus sp. nov. is described from females and males collected from forest leaf litter in Northern Iran. The new species can be easily recognised by its barbed setae j2 and z1, dorsal shield seta j5 located posterior to j6 and z6, a very wide ventri-anal shield, and the shape of the epistome. Geholaspis (G.) comelicensis Lombardini, 1962 is considered as a junior synonym of G. (G.) pauperior (Berlese, 1918). A new key for the separation of females of known species of Geholaspis (Geholaspis) is presented.